2021
DOI: 10.1073/pnas.2100021118
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of β-adrenergic regulation of Ca V 1.2: Rad-dependent and Rad-independent protein kinase A mechanisms

Abstract: L-type voltage-gated CaV1.2 channels crucially regulate cardiac muscle contraction. Activation of β-adrenergic receptors (β-AR) augments contraction via protein kinase A (PKA)–induced increase of calcium influx through CaV1.2 channels. To date, the full β-AR cascade has never been heterologously reconstituted. A recent study identified Rad, a CaV1.2 inhibitory protein, as essential for PKA regulation of CaV1.2. We corroborated this finding and reconstituted the complete pathway with agonist activation of β1-AR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 72 publications
2
29
0
Order By: Relevance
“…Recent studies have now shown bona fide physiological relevance for Rad as being a key player in the potentiation of CaV1.2 channel currents during b-adrenergic regulation of cardiomyocytes and HEK cells, as mediated by cAMP and protein kinase A (Ahern et al, 2019;Liu et al, 2020). Our recent work extended this finding, where we showed involvement of Rad in both b1-or b2-mediated adrenergic regulation of CaV1.2 in Xenopus oocytes (Katz et al, 2021). Like Rad, other RGK proteins may play similar physiological role(s) in b-adrenergic regulation of other tissues.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Recent studies have now shown bona fide physiological relevance for Rad as being a key player in the potentiation of CaV1.2 channel currents during b-adrenergic regulation of cardiomyocytes and HEK cells, as mediated by cAMP and protein kinase A (Ahern et al, 2019;Liu et al, 2020). Our recent work extended this finding, where we showed involvement of Rad in both b1-or b2-mediated adrenergic regulation of CaV1.2 in Xenopus oocytes (Katz et al, 2021). Like Rad, other RGK proteins may play similar physiological role(s) in b-adrenergic regulation of other tissues.…”
Section: Discussionsupporting
confidence: 75%
“…No significant differences (P=0.138) in IBa were observed between full length CaVβ2b, CaVβ2b-core and CaVβ2bcore with the GS-linker on its C-terminus (Fig. S1 and (Katz et al, 2021)). Therefore, all CaVβcore-Gem chimeras were analyzed in comparison with the CaVβ functional core-GS linker construct.…”
Section: Part Of the Gem G-domain And C-terminus Exhibit A Combined I...mentioning
confidence: 95%
See 2 more Smart Citations
“…To do so, we co-expressed hGluN1a with different mixtures of hGluN2B- wt and hGluN2B-G689C or -G689S mRNAs in Xenopus oocytes (i.e. mRNA titrations [ Berlin et al, 2020 ; Berlin et al, 2011 ; Yakubovich et al, 2015 ; Peleg et al, 2002 ; Katz et al, 2021 ]) and assessed glutamate dose-responses (see Materials and methods). When large mRNA amounts of hGluN2B- wt were co-expressed with very low amounts of hGluN2B-G689C (mRNA ratio: ~16:1, denoted wildtype-high; wt H ), we recorded large currents that readily responded to glutamate ( Figure 4a,b ; wt H ).…”
Section: Resultsmentioning
confidence: 99%